Polybenzimidazole membrane for efficient copper removal from aqueous solutions. Issue 9 (8th April 2022) - Coppola, Roxana E.; Lozano, Hernán E.; Contin, Mario; Canneva, Antonela; Molinari, Fabricio N.; Abuin, Graciela C.; D'Accorso, Norma B.
Abstract : Thin films of poly(2, 5‐benzimidazole) (ABPBI) polymer were prepared by the casting method, and sorption studies with aqueous CuSO4 solutions were performed. Surface interaction between Cu(II) and the membrane was studied using spectroscopic analysis (Fourier transform infrared, Raman and X‐ray photoelectron), showing a strong interaction through nitrogen groups of ABPBI and Cu(II). The best conditions for Cu(II) uptake were at pH = 5 and a soaking time of 60 min. In these conditions, the sorption isotherm was best fitted by the Langmuir equation and the maximum sorption capacity was estimated to be 1.5 mmol g −1 . Due to sorption pH dependency, elution studies using hydrochloric acid solution were carried out, showing an almost complete removal of bonded Cu(II) when immersing the ABPBI membrane in the acidic solution. Surface morphology of membranes was studied using scanning electron microscopy–energy‐dispersive X‐ray spectroscopy, showing no major changes with sorption and elution experiments. These results show that ABPBI can be considered as an alternative polymer for the development of new materials for the removal of heavy metals. © 2022 Society of Industrial Chemistry. Abstract : Thin films of poly (2, 5‐benzimidazole) (ABPBI) polymer were prepared and employed for copper removal from aqueous solutions in a pH‐dependent process.